The Duration of Hemodialysis and its Implication to Barthel Score and Laboratory Parameters among End Stage Renal Disease Patients - Jahidi, Savero Mizan; Mardiana, Nunuk; Wardhani, Indrayuni Lukitra (Universitas Brawijaya, 2021)
Background: While it was proven that hemodialysis for treating patients with end stage renal disease (ESRD) provided the reduced mortality rate, the reports on its adequacy in the context of laboratory parameters and psychological function were limited. Aim: To assess the implication of hemodialysis duration on Barthel score and laboratory parameters among ESRD patients. Â Methods: During the period, a cross-sectional study was conducted at Dr. Soetomo General Hospital. Information related to age, gender, history of hypertension, history of diabetes mellitus, and the levels of hemoglobin, albumin, calcium, and phosphor were retrieved from medical records. While, we performed the interview to each participant using Barthel index questionnaire to assess the function independence. We used multiple logistic regression analysis to determine the correlation and estimate of effect. Results: We totally include we included 65 patients with the hemodialysis duration of more than one year and 16 patients with the hemodialysis duration of less than one year. Our results found that the higher levels of albumin and hemoglobin were observed in patients with hemodialysis duration of more than one year. While, the duration of hemodialysis did not affect the Barthel score and serum mineral parameters. Conclusion: Â The duration of hemodialysis of more than one year is associated with the improvement of albumin and hemoglobin levels